Rapid degradation of left ventricular function after permanent right ventricular pacing in patients with high-grade atrioventricular block - Setiawan, Dion; Prasetya, Indra; Anjarwani, Setyasih; Rizal, Ardian (Heart Science Journal, 2025)
Background: Permanent right ventricular (RV) pacing is a standard for high-grade atrioventricular (AV) block treatment. However, it may result in left ventricular (LV) dilatation, systolic dysfunction, and heart failure (HF) as a consequence of ventricular dyssynchrony and an abnormal myocardial contraction pattern. Pacing-induced cardiomyopathy (PICM) can develop months or years after implantation of a permanent pacemaker (PPM) in patients who have long-term and high-burden RVP. Case Illustration: We reported a case of a 56 years old Asian female having a record of PPM on VVIR mode implantation due to a high grade AV block presented with shortness of breath and bilateral leg swelling. Conclusion: Echocardiography showed a significant decrease in LV systolic function less than two years after PPM implantation. Coronary angiography showed widely patent vessels; subsequently, His-Bundle Pacing (HBP) was scheduled on the patient.